Sustainable Wastewater Treatment Systems - Herrera-Melián, José Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Water is one of the main concerns of modern societies. Climate change will significantly complicate access to quality water for millions of people worldwide and the threat of contamination of aquatic resources by poor wastewater management is real and growing fast. Therefore, there is an urgent need to develop efficient and sustainable wastewater treatment methods. Although there are numerous water treatment methods, not all of them are equally sustainable, be it environmentally, economically or ethically. For this book, some of the latest advances in sustainable wastewater treatments were collected and 13 articles selected. The selected articles deal with aspects such as the removal of nanoparticles, the applicability of constructed wetlands, the recovery/removal of wastewater, the use of low-cost bio-sorbents, the optimization of activated sludge, the application of advanced oxidation technologies, and the modeling of reverse osmosis systems. This book will give the reader an idea of the latest trends in the sector of sustainable wastewater treatment.